Hubungan Persepsi Efek Samping IUD dengan Minat Ibu dalam Menggunakan KB IUD: Hubungan Persepsi Efek Samping IUD dengan Minat Ibu dalam Menggunakan KB IUD - Iskandar, Muli; Hayati, Ida (Chakra Brahmanda Lentera Institute, 2026)
Uncontrolled population growth may lead to various social and health problems. The Family Planning (FP) program is one of the key strategies to control population growth, including through the use of Intrauterine Devices (IUDs), which are effective and long-acting contraceptive methods. However, the utilization of IUDs in Indonesia remains low, partly due to negative perceptions regarding their side effects. This study aimed to determine the relationship between perceptions of IUD side effects and mothers’ interest in using IUD contraception in the working area of Muara Wahau 1 Community Health Center. This study employed a quantitative correlational design with a cross-sectional approach. A total of 56 non-IUD family planning acceptors were selected using accidental sampling. Data were collected using validated and reliable questionnaires measuring perceptions of IUD side effects and interest in IUD use. Data analysis was performed using univariate and bivariate methods with the Chi-Square test at a significance level of 0.05. The results showed that most respondents had negative perceptions of IUD side effects (82.1%) and low interest in using IUD contraception (82.1%). Among respondents with negative perceptions, the majority demonstrated low interest in IUD use (73.2%). The Chi-Square test revealed a p-value of 0.003 (p<0.05), indicating a statistically significant relationship between perceptions of IUD side effects and mothers’ interest in using IUD contraception. In conclusion, negative perceptions regarding IUD side effects are associated with lower maternal interest in adopting IUD contraception. Therefore, educational programs, counseling, and accurate information provided by healthcare professionals are needed to improve positive perceptions and increase the utilization of long-acting contraceptive methods such as IUDs.